PENDIDIKAN NILAI DAN KARAKTER UNTUK KOMUNITAS GURU BELAJAR NUSANTARA KABUPATEN BANYUMAS DI PURWOKERTO, JAWA TENGAH - Aripin Tambunan; Alexander Aur; Fitzerald Kennedy Sitorus; Ferdinandus Butar-butar; Enggar Pribadi (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
The goal of this study is to reveal the importance of comprehensive values and character education by teachers. Education plays a significant role in shaping students as whole human beings, which is why values and character education is not merely about making students behave well or obey existing moral values. Rather, it is about enabling students to express their character, which develops through the integration of their thoughts, feelings, desires, and actions. This process is achieved through the internalization of values and character, so that all dimensions of humanity can grow and be shaped into well-rounded individuals. Meanwhile, the context (needs) of this study is to answer the problems caused by the crisis of values as expressed by Wawan Wardiana from the Integrity Assessment Survey. To achieve the objectives in this context, teachers in the Nusantara Learning Community (KGBN) in Banyumas Regency need to receive values education training through a process of internalization using the value transmission method. To achieve the desired results, a qualitative case study research method was used. The results of this study can improve the understanding and competence of KGBN teachers in conducting values and character education through the internalization of values and character by means of value transmission.